The impact of event marketing and social media marketing on brand awareness of MSMEs in Ambon City - Saununu, Siska Jeanete; Reken, Feky; Tubalawony, Jacsy; Tabelessy, Walter (Jurnal Mantik, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are one of the main pillars of regional economies that need to strengthen their competitiveness through effective marketing strategies such as event marketing and social media marketing. This study aims to analyze the effect of these two strategies on brand awareness of MSMEs in Ambon City. The research employed a quantitative method with an associative approach, involving 100 respondents who had attended MSME events or interacted with MSME promotions through social media. Data were collected using questionnaires and analyzed using multiple linear regression with the JASP software. The findings show that event marketing has a positive and significant effect on brand awareness (p < 0.05), as it creates real experiences and emotional connections between consumers and brands. Similarly, social media marketing also has a positive and significant effect on brand awareness (p < 0.05), particularly through consistent promotional activities and creative content on platforms such as Instagram, TikTok, and Facebook. Both strategies complement each other in strengthening consumer recognition and recall of brands. These results highlight the importance of integrating offline and online marketing activities to expand market reach and build a strong brand image for MSMEs in society.